Pengaruh Sanksi Perpajakan, Kesadaran Wajib Pajak dan Tingkat Pendapatan Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Maria Oktavia Femi Wea (Yayasan Literasi Ilmiah Indonesia, 2022)
This study aims to prove the effect of Tax Sanctions, Taxpayer Awareness and Income Levels on Individual Taxpayer Compliance (Case Study of Individual Taxpayers at KPP Pratama Yogyakarta). This research is a quantitative research. The sample of this study is an individual taxpayer registered at KPP Pratama Yogyakarta. The sample was selected by purposive sampling method with certain criteria. The total sample is 170 respondents. Data analysis was carried out with validity and reliability tests, classical assumption tests and multiple linear regression analysis with IBM SPSS 23. The results of this study indicate that tax sanctions have a positive effect on individual taxpayer compliance, taxpayer awareness has a positive effect on individual taxpayer compliance and income levels on individual taxpayer compliance.